\(8^{2n}:4^{3n}\)
\(=\left(2^3\right)^{2n}:\left(2^2\right)^{3n}\)
\(=2^{6n}:2^{6n}\)
\(=2^{6n-6n}\)
82n:43n
= (23)2n:(22)3n
= 23.2n : 22.3n
= 26n : 26n
= 26n-6n
= 20 = 1
82n : 43n
= ( 23 )2n : ( 22 )3n
= 26n : 26n
= 26n-6n
= 20
= 1
Bạn bớt đi =1 dùm mình nhé mình lỡ tính ra luôn :v
82n : 43n
= ( 23 )2n : ( 22 )3n
= 26n : 26n
= 26n-6n
= 20
= 1
\(8^{2n}:4^{3n}\)
\(=\left(2^3\right)^{2n}:\left(2^2\right)^{3n}\)
\(=2^{6n}:2^{6n}\)
\(=2^{6n-6n}\)
\(=2^0\)
\(=1\)
Ko ghi lại đề bài ta có:
\(=\left(2^3\right)^{2n}:\left(2^2\right)^{3n}\)
\(=2^{6n}:2^{6n}\)
\(=2^6n-6n=2^0\)
\(=1\)
~Study well~ :)